Antioxidant Regulation and DNA Methylation Dynamics During Mikania micrantha Seed Germination Under Cold Stress - Cui, Can; Wang, Zhen; Su, Yingjuan; Wang, Ting (Frontiers in Plant Science, 2022)
As a primary goal, adaptation to cold climate could expand invasion range of exotic plants. Here, we aimed to explore the regulation strategy of M. micrantha seed development under cold stress through molecular physiology and multi-omics analysis. Significant increase of hydrogen peroxide, malondialdehyde and electrolyte leakage observed under cold stress revealed that oxidative damage within M. micrantha seed cells was induced in the initial germination phrase. Proteomic data underscored an activation of antioxidant activity to maintain redox homeostasis, with cluster of antioxidant proteins identified. Genomic-wide transcriptome in combination with time-series whole genome bisulfite sequencing mining elucidated that seven candidate genes target of DNA demethylation-dependent ROS scavenging were possibly associated with M. micrantha germ break. Progressive gain of CHH context DNA methylation identified in early germination phrase suggested a role of DNA methylation pathway, while an active DNA demethylation pathway was also initiated during late seed development, which was in line with the expression trend of methylation and demethylation related genes verified through qRT-PCR. These data pointed that cold-dependent DNA demethylation and antioxidant regulatory were involved together in restoring seed germination. The expression level of total 441 genes presented an opposite trend to the methylation divergence, while the expression of total 395 genes was proved to be negatively associated with their methylation levels. These data provided new insights into molecular reprograming events during M. micrantha seed development.